Recent Advances in the Molecular Imaging of Atherosclerosis - Larivière, Mélusine; Bonnet, Samuel; Lorenzato, Cyril; Laroche-Traineau, Jeanny; Ottonès, Florence; Jacobin-Valat, Marie-Josée; Clofent-Sanchez, Gisèle (Seminars in Thrombosis and Hemostasis, 2020)
Atherosclerosis is the major underlying cause of cardiovascular diseases, the prevalence of which is continuously increasing, thus currently standing as the leading global cause of death. This pathology gradually develops over the course of 50 or more years throughout the life of an individual under the influence of a vast number of factors, both environmental and pathophysiological. This wealth of factors has elicited much research into molecular imaging, with purely diagnostic purposes or with the hope of engineering an efficient theranostic tool. To these ends, diverse nanomaterials with desirable, tunable properties have been explored by different teams, as described in this review.
Keywords: molecular imaging; atherosclerosis; theranostic; nanomaterials